Enhanced depth imaging optical coherence tomography features of two types of Vogt–Koyanagi–Harada disease: fuzzy or lost pattern of the choroidal vasculature is of diagnostic value - Liu, Xinshu; Wang, Shuling; An, Yan; Zhang, Hao (Frontiers in Medicine, 2024)
Objective This study aimed to compare enhanced depth imaging optical coherence tomography (EDI-OCT) features of exudative retinal detachment (ERD) type and optic disc (OD) swelling type Vogt–Koyanagi–Harada (VKH) disease. Methods Hospitalized VKH patients were retrospectively reviewed and classified into the ERD type and the OD swelling type. The EDI-OCT features were then analyzed. Results The study included 32 ERD type and 15 OD swelling type VKH patients at the acute uveitis stage. The interval between the onset of ocular symptoms and the start of treatment in OD swelling type VKH disease was significantly longer compared to the ERD type (p < 0.001). A fuzzy or lost pattern of the choroidal vasculature was observed in 100% of VKH patients of both types. Moreover, high frequencies (greater than or equal to 50%) of fluctuations in the internal limiting membrane, interdigitation zone disruption, ERD, retinal pigment epithelium (RPE) folds, and ellipsoid zone disruption were observed in both types. Patients with OD swelling type VKH disease exhibited higher frequencies of OD swelling and hyperreflective substances above the RPE (p < 0.001 and p = 0.003, respectively), with lower frequencies of ERD and bacillary layer detachment (p = 0.012 and p < 0.001, respectively). At the convalescence stage, changes in the EDI-OCT images of 10 ERD type and 5 OD swelling type VKH patients were analyzed. The frequencies of the OCT features decreased with similar trends in both types of VKH disease. Conclusion Although ERD type and OD swelling type VKH disease have their own unique characteristics, they share common EDI-OCT features. The Fuzzy or lost pattern of the choroidal vasculature that indicates choroidal inflammation may serve as a diagnostic aid for VKH disease, especially for the OD swelling type and the early-stage ERD type.